Study of the Concrete”™s Compressive Strength Due to the Combined Effect oWater-cement ratio, the Coarse-fine Aggregate Ratio and the Source of the Aggregatesf the - Solís-Carcaño, Rómel; Moreno, Eric I.; Arcudia-Abad, Carlos (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Concrete”™s compressive strength is the main parameter used to control the quality of this material. From the beginning, when concrete was started to be used as structural material, it was found that the correlation between the water and the cement employed in the mixture had a great influence in the strength of concrete. Later on, other studies showed that the optimum combination between the fine and the coarse aggregate, seeking the highest compactness in the mixture, was also a factor that affects the concrete quality. This work presents a study about the concrete”™s compressive strength using three variables: the correlation between water and cement (w/c), the correlation between coarse and fine aggregates (c/f), and the aggregate”™s quarries. By means of a factorial design, the study used values of w/c and of c/f, in a possible range actually employed to make concrete, and several types of crushed limestone aggregates from the Yucatan Peninsula, which may not present the usual properties. It was found a significant influence of the w/c and the quarry in the compressive strength of concrete.Â Â